Determinants of consumer behavior in short food supply chains: a systematic literature review - Janna Herzig; Katrin Zander (Agricultural and Food Economics)
Abstract Short food supply chains (SFSCs) are increasingly regarded as promising alternatives to industrialized food distribution systems. They aim to create geographical, logistical, and social proximity between food producers and consumers. Despite extensive research on SFSCs in recent years, our understanding of how they can best be promoted is hindered by the lack of a unified approach in extant studies of consumer perspectives on SFSCs. The aim of this systematic literature review is thus to provide a comprehensive overview of the key determinants shaping consumer behavior around SFSCs. Following PRISMA guidelines, 30 peer-reviewed articles based on empirical research of SFSC consumers in the European Union were selected for analysis, applying Alphabet Theory as a theoretical framework. The findings emphasize the influence on consumer behavior of contextual factors, information availability, and trust, as well as the relevance of other commonly studied factors such as attitudes and sociodemographics. The review further highlights the importance of understanding how these factors interact to shape consumers’ perceptions of the costs and benefits of SFSCs. Based on these findings, the study gives recommendations to address the challenges identified and suggests directions for future research.